An Acceptance-Based Guided Self-Help Program for Weight Loss Maintenance in Adults Who Have Previously Completed a Behavioral Weight Loss Program: The SWiM Feasibility Study. - Jones, Rebecca A; Mueller, Julia; Richards, Rebecca; Woolston, Jennifer; Stubbings, Marie; Whittle, Fiona; Hill, Andrew J; Hughes, Carly A; Duschinsky, Robbie; Sharp, Stephen J; Chester, Michelle; Schwertel, Carlotta; et al. (Wiley, 2025)
BACKGROUND: Most weight lost during weight-loss programmes is eventually regained. Interventions based on Acceptance and Commitment Therapy (ACT) demonstrate good evidence for long-term weight loss, but are often costly and difficult to scale up. Guided self-help programmes delivered using technology and non-specialist coaches could increase scalability, but it is unclear whether delivering ACT-based interventions in this way is feasible and acceptable. METHODS: In this feasibility study, 61 people who recently completed a behavioral weight management intervention (BWMI) for weight management were randomly allocated to SWiM ("Supporting Weight Management": 4-month digital guided self-help ACT-based intervention for weight loss maintenance) or a standard care group (leaflet about maintaining weight loss) using a 2:1 allocation ratio. At baseline and 6 months, participants completed measures of weight, mental health, eating behavior, and other psychosocial variables. Participants completed an intervention evaluation questionnaire. At 3 and 6 months, qualitative interviews were conducted with participants from both trial arms and SWiM coaches. The analysis integrated statistics and thematic analysis, informed by the Medical Research Council (MRC) framework for process evaluations. Since this was a feasibility study, analyses focused on process outcomes instead of interpreting statistical significance. RESULTS: Eighty-eight percent (36/41) of participants allocated to SWiM completed at least the first session and 22 (54%) completed all sessions. At 6 months, mean weight change was -2.2 (+/-6.4 SD) kg in SWiM participants and +2.2 (+/-6.6) kg in standard care participants. Descriptively, eating behavior and mental health scores improved in SWiM participants but not in standard care participants. In interviews, SWiM participants noted that they reinforced their existing knowledge while acquiring new skills and strategies, which were felt to contribute to positive behavioral changes. CONCLUSION: The SWiM intervention is practical and well-received, and shows promise in supporting weight loss maintenance, though evaluation in a larger trial is needed to assess effectiveness. TRIAL REGISTRATION: ISRCTN12685964.
Publication status: Published
Keywords: acceptance and commitment therapy; digital; interventions; obesity; overweight; weight loss maintenance; weight management